Is sustainable certification's ability to combat greenwashing trustworthy? - Nygaard, Arne (Frontiers in Sustainability, 2023)
Introduction Certifications are widely recognized as important tools in addressing climate change, safeguarding human rights, and promoting environmentally sustainable practices. However, this critical review article draws attention to potential negative impacts associated with certifications. The purpose of this review is to highlight the risks and challenges associated with certifications despite their intended benefits. Methods The review draws on existing literature on certifications and their impacts, as well as empirical studies on the effectiveness of certifications in addressing climate change, safeguarding human rights, and promoting environmentally sustainable practices. Results The review finds that certifications can increase the perceived value of eco-friendly brands and consumer willingness to pay. However, the review also highlights the risks of greenwashing and free riding, which can undermine the intended benefits of certifications. Additionally, the institutional organization of certification systems may exhibit structural inertia, which may impede the integration of disruptive green technologies and market transitions. Discussion The potential negative impacts of certifications on addressing climate change, safeguarding human rights, and promoting environmentally sustainable practices should not be overlooked. It is essential to implement measures to mitigate the risks of eco-opportunism and to effectively combat greenwashing. The review suggests that certification systems should be designed to promote innovation and the adoption of new technologies, rather than being a barrier to change. Conclusion Certifications are important tools for addressing climate change, safeguarding human rights, and promoting environmentally sustainable practices. However, their potential negative impacts should be acknowledged and addressed. The review recommends implementing measures to mitigate the risks of eco-opportunism and to effectively combat greenwashing, while promoting innovation and the adoption of new technologies.